EFFECTS OF GEOMETRY AND MATERIAL FACTORS ON THE BEHAVIOR OF STIFFENED OFFSHORE PIPE STRUCTURES UNDER HYDROSTATIC PRESSURE - Widiyanto, Ilham; Prabowo, Aditya Rio; Muttaqie, Teguh; Muhayat, Nurul; Yaningsih, Indri; Tjahjana, Dominicus Danardono Dwi Pria; Juwana, Wibawa Endra; Miyazaki, Takahiko (Journal of Applied Engineering Science, 2022)
The world’s oil and gas sectors are diverse. They utilize offshore pipes to generate millions of barrels of oil and gas to meet global energy demands. In this study we identified the critical buckling load that occurred on a cylinder shell (also known as radial buckling). Offshore pipe design must meet several criteria, one of which is the requirement for pipes to withstand the external hydrostatic pressure of seawater. The overall buckling load is calculated using the axial compression loading and the pressure on the entire surface of the cylinder shell (radial compression). The finite element analysis (FEA) method is used in our simulation. FEA is run using ABAQUS/CAE software with the Riks algorithm. Different types of cylinder shells are used in the simulation: unstiffened, stringer-stiffened, and ring-stiffened. The cylinder shell is loaded based on the depth of the installation. The material composition of the shell is varied with API 5L X65, copper-nickel alloy, and HY100 steel. The diameter sizes used are 28" (711.2 mm), 30" (762 mm), and 32" (812.8 mm). The simulation results show a critical buckling load for each variation. The critical buckling load is determined by the Young’s modulus, geometric length, and moment of inertia. Based on the critical buckling loads generated, we also identify which cylinder shell composition is the strongest.